Use the substitution method:
2x - 6y = -12
x - 2y = -8
Then x = 2y - 8
Substitute in the first equation:
2(2y - 8) - 6y = -12
4y - 16 - 6y = -12
-2y = 4
y = -2
Now substitute y in one of the two equations given you prefer:
For example x-2*(-2) = -8
x + 4 = -8
x = -12
The solutions are x = -12 and y = -2
I believe the answer is 264, but if it’s not 11 and it’s 22 then the answer is 528!! Mark me brainliest please!!!!❤️
Answer:
12+x=12+4=16
3x+y=3*4+7=12+7=19
4y-10=4*7-10=28-10=18
1/2xy=1/2*4*7=28/2=14
Step-by-step explanation:
Answer:
Both answers are correct, depending on the angle taken as reference
Step-by-step explanation:
we know that
In a right triangle
The slope ratio of the triangle is equal to the function tangent
The function tangent in a right triangle is equal to the opposite side to the angle divided by the adjacent side to the angle
so
-----> Ben's ratio
and
------> Carlissa's ratio
therefore
The slope will depend on the angle taken as a reference
so
Both answers are correct, depending on the angle taken as reference.